(untitled) (New Jersey, 1996)
This leading, two-volume anthology represents America's literary heritage from the colonial times of William Bradford and Anne Bradstreet to the contemporary era of Saul Bellow and Alice Walker. Volume II begins with Walt Whitman and Emily Dickinson and moves through Toni Morrison. It reflects a continued emphasis on cultural plurality, and multiple selections by authors that enables readers to compare and contrast different works. Numerous editions in their entirety include Twain's Adventures of Huckleberry Finn; Crane's The Red Badge of Courage; William's The Glass Menagerie; Hansberry's A Raisin in the Sun; and Miller's Death of a Salesman. Also featured are shorter works—such as “How to Tell a Story,” by Mark Twain; Poems by Rita Dove; short stories by Sandra Cisneros, Louise Erdrich, and Toni Morrison. For modern scholars of America's literary history, and readers who simply love to read—especially the classics.
Keywords: American literature.,United States,Văn học Mỹ; Literary collections